2022
DOI: 10.3390/polym14224794
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Electric Circuit Analysis of Anisotropic Electrical Conductivity and Piezoresistivity of Carbon Nanotube Nanocomposites

Abstract: Electrical conductivity and piezoresistivity of carbon nanotube (CNT) nanocomposites are analyzed by nodal analysis for aligned and random CNT networks dependent on the intrinsic CNT conductivity and tunneling barrier values. In the literature, these parameters are assigned with significant uncertainty; often, the intrinsic resistivity is neglected. We analyze the variability of homogenized conductivity, its sensitivity to deformation, and the validity of the assumption of zero intrinsic resistivity. A fast al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Carbon nanotubes (CNTs) enhance polymer properties as a nanofiller and have been promising candidates to increase the electrical conductivities of epoxy-based nanocomposites with high precision and piezoresistive sensitivity [ 3 , 4 , 5 , 6 , 7 ]. Especially in the field of high-precision sensors [ 8 , 9 , 10 ], the influence of environment temperature [ 11 , 12 ] cannot be ignored for multiple polymer functionalities. Considering electrical properties, this phenomenon is commonly related to the temperature coefficient of resistance ( TCR ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon nanotubes (CNTs) enhance polymer properties as a nanofiller and have been promising candidates to increase the electrical conductivities of epoxy-based nanocomposites with high precision and piezoresistive sensitivity [ 3 , 4 , 5 , 6 , 7 ]. Especially in the field of high-precision sensors [ 8 , 9 , 10 ], the influence of environment temperature [ 11 , 12 ] cannot be ignored for multiple polymer functionalities. Considering electrical properties, this phenomenon is commonly related to the temperature coefficient of resistance ( TCR ).…”
Section: Introductionmentioning
confidence: 99%
“…The CNT intrinsic conductance and tunnelling (or contact) conductance between CNTs are the two basic types of conductance determining the electrical response of a CNT/ polymer nanocomposite [ 14 , 15 , 16 , 17 , 18 ]. Both are complementary one to another [ 9 ] when the leading mechanism of resistance is determined by many factors, first of all, chirality. Besides, the electrical behaviour of CNT networks is significantly influenced by CNT shapes, CNT wall count, functional surface groups, bundling, agglomeration, and CNT deformation at contacts–phenomena that are difficult to be described quantitatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNT minimal contact distance can, in principle, be affected by CNT compression. The effect of this on the homogenized conductivity was evaluated in [ 21 ] and found to be weak; therefore, the value of 0.34 nm is retained in the present calculations.…”
Section: A-cnt Films and Identification Of The Nano-structure Parametersmentioning
confidence: 99%
“…In [ 21 ], the present authors compared the influence of parameters defining different conductance mechanisms and found that g intr is the most influential one and has to be fitted in the first place. When this was completed, the use of most common values for the tunnelling resistance and inter-CNT contact distance gave good correspondence with the experimental measurements in [ 8 ].…”
Section: A-cnt Films and Identification Of The Nano-structure Parametersmentioning
confidence: 99%